Electric field and shape effect on the linear and nonlinear optical properties of multi-shell ellipsoidal quantum dots. (June 2016) - Shi, L.; Yan, Z.W.
Abstract: In the present work, the optical properties of GaAs/Al x Ga1− x As/GaAs multi-shell ellipsoidal quantum dot heterostructures with a shallow hydrogenic impurity in the presence of an external electric field have been studied. The results show how the linear and nonlinear optical absorption coefficients and refraction index changes are changed by the variations of the size and shape of the multi-shell structure. Moreover, how the optical properties of this structure are affected by the electric field has also been shown. The physical reasons for the results have been discussed in detail. Highlights: Electric field red shifts the peak positions of the ACs and RICs. Effect of electric field is obvious for the large core, shell and well regions. MSQDs with prolate case red shifts the peak positions of the ACs and RICs. MSQDs with oblate case blue shifts the peak positions of the ACs and RICs.